APLIKASI PENJADWALAN PIKET STAF KANTOR PADA AKADEMI KEPOLISIAN SEMARANG BERBASIS WEB - DWI SUSILO, ANDI; TRI HANDOKO, DRS.,M.KOM, WIDIYANTO (Information Technology and Telematics, 2018)
Abstract- Daily activities are easier with the presence of telecommunications devices called mobile phones. In addition to being used to communicate voice with the other person, the phone also has other capabilities, which can be used to send text messages more popular with the name of SMS. Applications that will be developed in this research is the application of picket scheduling on web-based Semarang Akpol. With this picket scheduling information app, the announcement of a manual picket schedule can be made into electronic scheduling, so that information errors can be avoided. The application of picket scheduling information is designed to be accessible via the web, and the system can send SMS reminder as a reminder that a certain day there is a picket schedule. System development method used in this research is prototype, system design using UML and system implementation using PHP, GAMMU and MySQL. The results in this study were picket scheduling application can send reminders as a reminder that particular day there were picket schedule before 3 day itinerary to the police picket automatically Semarang Police Academy Keywords – Scheduling, Reminder System, Akpol Semarang GAMMU, PHP, MySQL DAFTAR PUSTAKA Aditya, A.N, (2010) Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, Bekasi Budicahyanto, D. (2009) SMS Gateway,PT.Elex Media Komputindo,Jakarta Ciptadi, P.W., Rumani, R., Mulyana, R., (2008) Membangun Aplikasi SMS Gateway Untuk Layanan Informasi Tagihan Telepon Dan Transaksi Pembayaran Rekening Menggunakan Operating System Linux, Skripsi, Universitas Telkom Febriyus, A., (2013) Rancang Bangun Aplikasi E-Reminder Services (Layanan Pengingat Elektronik) Untuk Kegiatan Dosen (Study Kasus Jurusan Teknik Informatika Uin Suska Riau), Skripsi, Universitas Islam Negeri Sultan Syarif Kasim Riau Ferdiansyah, Y., (2014) Pemanfaatan Google Calendar Sebagai SMS Alert  Dalam Sistem Monitoring Jaringan Komputer  (Studi Kasus : Jaringan Komputer Universitas Bengkulu), Skripsi, Universitas Bengkulu Henderi (2008) Unified Modelling Language, Raharja Enrichment Centre (REC), Tangerang Ladjamudin, A.B, (2005), Analisis dan Desain Sistem Informasi, Graha Ilmu, Yogyakarta Mulyanto, A (2009) Sistem Informasi Konsep & Aplikasi, Pustaka Pelajar, Yogyakarta Prasetyo, D.D, (2006) Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta Sommerville, I., (2003) Software Enginneering, Erlangga, Yogyakarta Wikipedia., (2017), Situs Web, https://id.wikipedia.org/wiki/Situs_web diunduh pada tanggal 16/11/2017